Reinforcing Positive Behavior through Attention Cue Point Sheet - Maria Carmela Ablero; Ruel Bonganciso (Journal of Elementary and Secondary School, 2026)
This study utilized the Plan-Do-Study-Act (PDSA) Action Research Model by Shewhart and Deming to address off-task behaviors in a grade 7 classroom. A survey initially identified ten common disruptive behaviors, including sleeping and talking to seatmates. To encourage positive behavior, an Attention Cue Point Sheet was implemented, along with dynamic seating arrangements based on student preferences. On Day 1, high incidences of off-task behaviors were observed, with 45% of students goes in and out without permission, and 50% talking to seatmates as the highest. By Day 2, these behaviors significantly reduced, with only 20% of students goes in and out without permission and 7.5% students talking to their seatmates. Improvements continued on Day 3, and by Day 4, off-task behaviors were nearly eliminated. This four-day intervention, featuring daily monitoring and personalized feedback following the sandwich feedbacking method, substantially reduced disruptive behaviors. The study highlights the effectiveness of the PDSA model and positive reinforcement strategies in promoting positive classroom behavior and creating a conducive learning environment.